Open pit mine planning with degradation due to stockpiling - Rezakhah, Mojtaba; Newman, Alexandra (Computers & operations research, 2020)
•We extend a linear-integer mine-planning model that considers stockpiling.•We account for degradation within the stockpile(s).•We compare results from this model on a data set from an operational mine.•Degradation decreases the value that a stockpile provides by as much as 69%. The open pit mine production scheduling with stockpiling (OPMPS+S) problem decides when to extract each notional, three-dimensional block of ore and/or waste in a deposit. In addition, this problem determines whether to send each block to a processing plant, to a stockpile, or to a waste dump. The objective function maximizes net present value, subject to constraints such as precedence, and capacities for mining and processing. Because the material within the stockpile is exposed to the environment, time-dependent changes may occur in the material’s properties, which results in increased processing costs or, equivalently, a net loss of value. We extend a linear-integer mine-planning model that considers stockpiling to account for degradation within the stockpile(s). We compare results from this model on a data set from an operational mine to more commonly used, yet less detailed, models that provide lower and upper bounds on the net present value. We show that the material degradation within a stockpile has an impact on the value that a stockpile provides. Specifically, by considering 5% and 10% annual degradation for our instances, we observe that the value that a stockpile provides decreases by 37% and 69%, respectively, relative to the computed value of a stockpile without degradation.